Equity of health financing in Indonesia: A 5-year financing incidence analysis (2015-2019) - Qinglu Cheng; Augustine Asante; Dwidjo Susilo; Aryana Satrya; Nicola Man; Rifqi Abdul Fattah; Manon Haemmerli; Soewarta Kosen; Danty Novitasari; Gemala Chairunnisa Puteri; Eviati Adawiyah; Andrew Hayen; et al. (Elsevier, 2022)
Summary: Background: In 2014, Indonesia launched a single payer national health insurance scheme with the aim of covering the entire population by 2024. The objective of this paper is to assess the equity with which contributions to the health financing system were distributed in Indonesia over 2015 - 2019. Methods: This study is a secondary analysis of nationally representative data from the National Socioeconomic Survey of Indonesia (2015 - 2019). The relative progressivity of each health financing source and overall health financing was determined using a summary score, the Kakwani index. Findings: Around a third of health financing was sourced from out-of-pocket (OOP) payments each year, with direct taxes, indirect taxes and social health insurance (SHI) each taking up 15 - 20%. Direct taxes and OOP payments were progressive sources of health financing, and indirect tax payments regressive, for all of 2015 - 2019. SHI contributions were regressive except in 2017 and 2018. The overall health financing system was progressive from 2015 to 2018, but this declined year by year and became mildly regressive in 2019. Interpretation: The declining progressivity of the overall health financing system between 2015 - 2019 suggests that Indonesia still has a way to go in developing a fair and equitable health financing system that ensures the poor are financially protected. Funding: This study is supported through the Health Systems Research Initiative in the UK, and is jointly funded by the Department of International Development, the Economic and Social Research Council, the Medical Research Council and the Wellcome Trust.